Dispersive liquid–liquid microextraction and HPLC to analyse fluoxetine and metoprolol enantiomers in wastewaters - Ribeiro, Ana R. (2016)
Sample extraction is a major step in environmental analyses due both to the high complexity of matrices and to the low concentration of the target analytes. Sample extraction is usually expensive, laborious, time-consuming and requires a high amount of organic solvents. Actually, there is a lack of miniaturized methodologies for sample extraction and chiral analyses. Here, we developed a dispersive liquid-liquid microextraction (DLLME) to extract the pharmaceuticals fluoxetine and metoprolol, as models of basic chiral compounds, from wastewater samples. Compounds were then analysed by enantioselective high-performance liquid chromatography. We monitored the influence of sample pH, extracting and dispersive solvent and respective volumes, salt addition, extracting and vortexing time. The DLLME method was validated within the range of 1-10 A mu g L-1 for fluoxetine enantiomers and 0.5-10 A mu g L-1 for metoprolol enantiomers. Accuracy ranged from 90.6 to 106 % and recovery rates from 54.5 to 81.5 %. Relative standard deviation values lower than 7.84 and 9.00 % were obtained for intra- and inter-batch precision, respectively.